Trust and citizen participation in community-based monitoring system: An experimental evidence from Bangladesh - Rabbani, Mehnaz; Rahman, Semab; Tasneem, Dina (Elsevier, 2024)
This article was published in The Journal of Behavioral and Experimental Economics [©2022 Rights managed by Elsevier] and the definite version is available at: https://doi.org/10.1016/j.socec.2022.101884 The Article's website is at: https://www.sciencedirect.com/science/article/abs/pii/S2214804322000581?via%3Dihub